Boundedly Rational Decision Emergence - A General Perspective and Some Selective Illustrations - Werner Güth (Center for Economic Studies and ifo Institute (CESifo), 2000)
A general framework is described specifying how boundedly rational decision makers generate their choices. Starting from a Master Module which keeps an inventory of previously successful and unsuccessful routines several submodules can be called forth which either allow one to adjust behavior (by Learning Module and Adaptation Procedure) or to generate new decision routines (by applying New Problem Solver). Our admittedly bold attempt is loosely related to some stylized experimental results.
Keywords: 330